Assessment of environmental impacts and risk of incidents during construction and operation of solar power projects - Le My Nhan Nguyen; Kim Ngan Luong; Thi Le Na Pham; Phi Hung Tran (Petrovietnam Journal, 2021)
The article assesses the impacts of large-scale solar power projects on the environment at each stage of project implementation, including the management and treatment of waste from expired solar panels, and incidents occurring during the construction and operation of solar power projects. The impacts are identified and evaluated, which will serve as a basis for analysing the project’s effectiveness in the context of economic development associated with the goal of sustainable development of the natural environment and the society. On that basis, the authors propose research directions to help state management agencies promulgate relevant regulations in the process of approval as well as environmental management and monitoring of solar power projects in the future.